Internalization of Religious Values to Students Based on Extracurricular Activities in Junior High School - Minhaji, Minhaji; Hosaini, Hosaini; Maktumah , Luluk (International Journal of Multidisciplinary Research of Higher Education, 2024)
Internalization of religious values in schools is very important so that students not only understand them, but are able to practice them in various ways of life. Classroom learning has not been able to provide capital for students to answer the challenges faced in the millennial era, considering that classroom learning focuses more on developing cognitive aspects, while affective and psychomotor skills occur very little. This research aims to internalize Islamic religious values to students through extracurricular activities. This research uses a qualitative method with a phenomenological approach to explore the process of internalizing religious values through Islamic extracurricular activities at the junior high school level in Indonesia. One school in Indonesia took anticipatory steps by designing extracurricular activities by prioritizing religious activities to strengthen student enrichment and deepening of religious values. Data sources in the study included students who were active in extracurricular activities, supervising teachers, school principals, and parents. Data collection was conducted through in-depth interviews, participant observation and documentation. The research findings show that the internalization of religious values carried out includes the values of faith, sharia, and morals with exemplary methods, habituation, advice and supervision; and the internalization process goes through three stages, namely; transformation, transaction and transinternalization. These findings are associated with previous theories that have implications or contribute in a form that supports and strengthens previous theories.